The last stand [videorecording (DVD)] - Kim, Chi-un, 1964-; Schwarzenegger, Arnold; Whitaker, Forest; Noriega, Eduardo, 1973-; Alexander, Jaimie (Lionsgate, 2013)
After leaving his LAPD narcotics post, Sheriff Ray Owens moved and settled into a life fighting what little crime takes place in sleepy border town Sommerton Junction. That peaceful existence is shattered when Gabriel Cortez, one of the most notorious drug kingpins, makes an escape from the FBI. Cortez begins racing towards the US-Mexico border, straight through Sommerton Junction.